Oxford Research Encyclopedia of Communication 2019
DOI: 10.1093/acrefore/9780190228613.013.881
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Cooperation in Journalism

Abstract: The journalism industry has used technology and cooperation to convey information around the world since the mid-1800s when six American newspapers aligned to form the Associated Press. The nonprofit news agency was a business collaboration that allowed members to share content with one another. Cooperation in journalism was not always compatible with the industry’s traditional business model, however, which valued exclusivity. As technology progressed, cooperation grew ever easier and more productive. The ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…There remains a dearth of academic insight into this recent restructuring of investigative journalism (cf. Carson & Farhall, 2018;Heft, Alfter, & Pfetsch, 2017;Konieczna, 2018;Konow-Lund, Gearing, & Berglez, 2019;Sambrook, 2018). In the aftermath of the Panama Papers story (2016), however, some academic and practitioner contributions to the field of research have emerged (Alfter, 2019;Graves & Shabbir, 2019;Stonbely, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There remains a dearth of academic insight into this recent restructuring of investigative journalism (cf. Carson & Farhall, 2018;Heft, Alfter, & Pfetsch, 2017;Konieczna, 2018;Konow-Lund, Gearing, & Berglez, 2019;Sambrook, 2018). In the aftermath of the Panama Papers story (2016), however, some academic and practitioner contributions to the field of research have emerged (Alfter, 2019;Graves & Shabbir, 2019;Stonbely, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The analyses carried out to date both within organizations and at the national level have certainly proved useful for understanding the current meaning of data journalism and the characteristics and public implications of this practice. However, it seems necessary to throw light on the context, experience and implications for audiences of the bellwether international collaborative and investigative data journalism projects carried out so far, considering their growing importance in both theory and practice (Konow-Lund, Gearing & Berglez, 2019).…”
Section: Data Journalism: Definition and Researchmentioning
confidence: 99%
“…While researchers have long argued that news-room workers tend towards a deterministic view of technology (Örnebring, 2016, 2010, 2009), times have changed, and new affordances (and a new appreciation of existing affordances) may be impacting the field, leading to, among other things, new forms of interdisciplinary collaboration. Here, collaboration is understood to mean a shared effort towards a common end (Konow-Lund et al, 2019). Astrid Gynnild (2013) emphasises the porous boundaries between various interdisciplinary actors in journalism, such as reporters and programmers.…”
Section: Technological Affordances and Valuesmentioning
confidence: 99%
“…Recent studies have indicated that the 'lone wolf' era of investigative journalism is coming to an end, as watchdog journalism is reconstructed across borders with a special focus on collaboration, digital technology and networking (Berglez & Gearing, 2019;Konow-Lund, Gearing, & Berglez, 2019;Sambrook, 2018;Lewis, 2018;Alfter, 2019). In just the past two decades, we have seen an increase in journalistic innovation involving users (Harhoff & Lakhani, 2016), while fewer studies have focused on how traditional and emerging forms of investigative journalism seek to involve participants and users in watchdog journalism aiming to hold power to account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation